Myeloma bone disease: from biology findings to treatment approaches - Terpos, Evangelos; Ntanasis-Stathopoulos, Ioannis; Dimopoulos, Meletios A (Blood, 2019)
Bone disease is a cardinal complication of multiple myeloma that affects quality of life and survival. Osteocytes have emerged as key players in the development of myeloma-related bone disease. Along with other factors, they participate in increased osteoclast activity, decreased osteoblast function, and immunosuppressed marrow microenvironment, which deregulate bone turnover and result in bone loss and skeletal-related events. Denosumab is a novel alternative to bisphosphonates against myeloma bone disease. Special considerations in this constantly evolving field are thoroughly discussed.